2010
DOI: 10.1348/135532509x473913
|View full text |Cite
|
Sign up to set email alerts
|

Female juvenile arsonists: An exploratory look at characteristics and solo and group arson offences

Abstract: Purpose. This study is an examination of a sample of 114 female juveniles charged with arson in a large juvenile justice system. The purpose of this study is to contribute to the limited descriptive literature about female juvenile arsonists. Methods. Female juvenile arsonists who had been charged with an arson were explored regarding their experiences of family disorganization, abuse and neglect, school issues, substance abuse, mental health, and crime characteristics. Group and solo arson offending was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Parents are often absent or indifferent (Davis & Lauber, 1999), exercising limited behaviour monitoring, and expressing little affection or acceptance towards their children (Kazdin & Kolko, 1986; Kolko & Kazdin, 1990). Many juvenile arsonists are characterized by poor social skills, low academic achievement (Del Bove et al , 2008), and negative peer involvement that may result in committing arson with peers (Hickle & Roe‐Sepowitz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Parents are often absent or indifferent (Davis & Lauber, 1999), exercising limited behaviour monitoring, and expressing little affection or acceptance towards their children (Kazdin & Kolko, 1986; Kolko & Kazdin, 1990). Many juvenile arsonists are characterized by poor social skills, low academic achievement (Del Bove et al , 2008), and negative peer involvement that may result in committing arson with peers (Hickle & Roe‐Sepowitz, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing research support for the idea that psychological disturbance of some sort is more prevalent among lone actor terrorists than group‐based terrorists. (Gruenewald, Chermak, & Freilich, ; Hewitt, ) The same appears to be true for criminals who act alone, as opposed to those in groups (Bijleveld & Hendriks, ; Hickle & Roe‐Sepowitz, ). We have found no such studies of individuals who commit felonious assaults on police officers, but hypothesize that the results would be similar.…”
Section: Discussionmentioning
confidence: 94%
“…Using vastly different samples, studies comparing lone and group rapists have found that the former tended to be significantly older (Bijleveld and Hendriks, ; Hauffe and Porter, ; Ullman, ; Wright and West, ), significantly more likely to be married and have children, significantly less likely to have a history of substance abuse (Hauffe and Porter, ), significantly more likely to have previous convictions and problematic personality structures (Bijleveld and Hendriks, ), and significantly more likely to be employed (Ullman, ). Hickle and Roe‐Sepowitz's () study of female juvenile arsonists found solo offenders more often came from unstable homes; more often experienced school difficulties, behavioral problems, and negative emotions; and expressed suicidal thoughts more regularly (the latter finding is particularly relevant to Gruenewald et al's study when we consider their finding that lone offenders were more likely to die in the commission of their offense).…”
Section: Research Implications and Considerationsmentioning
confidence: 86%